Pro HTML5 programming : powerful APIs for richer Internet application development - Lubbers, Peter (Expert's voice in Web development., 2010)
HTML5 is here, and with it, web applications take on a power, ease, scalability, and responsiveness like never before. In this book, developers will learn how to use the latest cutting-edge HTML5 web technology - available in the most recent versions of modern browsers - to build web applications with unparalleled functionality, speed, and responsiveness. * Explains how you can create real-time HTML5 applications that tap the full potential of modern browsers * Provides practical, real-world examples of HTML5 features in action * Shows which HTML5 features are supported in current browsers * C.